THE The Impact of Tablet Devices on English Teaching in Intermediate-Phase Classrooms - Chinengundu, Tawanda; Lowe, Jordan (JEET, Journal of English Education and Technology, 2024)
Research shows that mobile computing like iPads and tablets has gained popularity in classrooms. While prior research has explored technology in education broadly, this study specifically focuses on the impact of tablets on English language teaching within the intermediate phase. The study was underpinned by the Technological Pedagogical Content Knowledge model. A qualitative approach was employed in this study for contextual inquiry, enabling a deeper understanding of the impact of tablet integration on English teaching and learning. The sample for this research consisted of five teachers selected through convenience sampling. These participants taught English within the intermediate phase at schools in Mpumalanga province, South Africa. Semi-structured interviews with open-ended questions were used to inquire educators about their teaching methods, challenges, and how tablets have affected student learning. Data were analyzed by developing themes. The findings revealed that tablet integration led to improvements in pedagogical practices, and increased student engagement. However, challenges such as limited technological infrastructure, the need for teacher training, and the potential for tablets to introduce distractions and hinder critical thinking among students were established. We argue that to be effective, tablet integration requires equitable access, curricular knowledge, teaching methodologies, technological skills, and individualized learning for every student.